Ocular myocysticercosis: Favorable outcomes with early diagnosis and appropriate therapy - Chopra, R; Kapoor, H; Chopra, A (Nepalese Journal of Ophthalmology, 2012)
Background: Ocular myocysticercosis is rare and a high index of suspicion is required for its diagnosis. Objective: To describe clinical characteristics and treatment outcome of ocular myocysticercosis. Cases: We describe a series of three patients who had different clinical presentations of ocular myocysticerocosis namely diplopia, restricted ocular motility and subconjunctival cyst. The treatment with oral albendazole and prednisolone was effective in all three cases. Conclusion: Favorable outcomes can be achieved with a high index of suspicion, early diagnosis and treatment with oral albendazole and prednisolone in patients with ocular myocysticercosis.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6551 Nepal J Ophthalmol 2012; 4 (2): 315-318